Double-setting alpha-tricalcium phosphate cement provided with interconection channels in rabbits after enucleation: a potential implant for the anophthalmic socket - Gomes Junior, D. C. [UNESP]; Oriá, A. P.; Dórea Neto, F. A.; Santos, L. A. dos; Estrela-Lima, A.; Barbosa, V. F.; Costa Neto, J. M.; Laus, J. L. [UNESP]; Daleck, C. R. (Universidade Federal de Minas Gerais, Escola de Veterinária, 2015)
The purpose of this study was to evaluate the macroscopy and microstructure of a double setting alpha-tricalcium phosphate bone cement sphere provided with interconnection channels (alpha-TCP-i), as well as the integration of the implant with the rabbits' orbital tissue, through macroscopic analysis and histopathology. The external and internal surfaces of the alpha-TCP-i were evaluated macroscopically and by electron microscopy. Twelve New Zealand rabbits received 12mm implants of alpha-TCP-i following enucleation of the left eye. The clinical assessment was undertaken daily during the first 15 days, followed by fortnightly assessment until the end of the study period. For the morphological analysis, exenteration was performed in 3 animals per experimental period (15, 45, 90 and 180 days). The external and internal surfaces of the implant appeared solid, smooth and compact, with six channels which interconnected centrally. The micro-architecture was characterized by the formation of columns of hexagonal crystals. No signs of infection, exposure, dehiscence of sutures or extrusion of the implant were noted in any of the animals during the entire period of the study. The morphological evaluation demonstrated the presence of a thin capsule around the implant, from whence appeared fibro-vascular projections, which penetrated it through the interconnecting channels. In the first days after the insertion of the implant, an intense inflammatory reaction was noted. At 180 days, however, there were no signs of inflammation. The alpha-tricalcium phosphate cement implant was well tolerated in this rabbit model and appeared to be relatively inert with some fibrovascular ingrowth through the large channels.

Avaliaram-se a macroscopia e a microestrutura de esferas compostas por cimento ósseo de alfa-fosfato tricálcico de dupla pega munido de canais de interconexão (alfa-TCP-i) e a integração do implante ao tecido orbital de coelhos através de análise macroscópica e histopatológica. A superfície interna e externa do alfa-TCP-i foi avaliada macroscopicamente e por microscopia eletrônica. Após enucleação do bulbo ocular esquerdo, 12 coelhos da raça Nova Zelândia receberam implantes do alfa-TCP-i com 12mm de diâmetro. A avaliação clínica foi realizada diariamente nos primeiros 15 dias e depois a cada quinze dias até o fim do período de estudo. Para análise morfológica, seguiu-se a exenteração de três animais por período experimental (15, 45, 90 e 180 dias). As superfícies externa e interna do implante mostraram-se compactas, sólidas e lisas, com seis canais que se interconectavam centralmente. A microarquitetura caracterizou-se pela formação de colunas de cristais hexagonais. Sinais de infecção, exposição, deiscência de sutura ou extrusão não foram notados em nenhum dos animais durante o período de estudo. A análise morfológica revelou a presença de fina cápsula ao redor do implante de onde surgiram projeções fibrovasculares que o penetraram através dos canais de interconexão. Nos primeiros dias após a inserção das esferas, notou-se intensa reação inflamatória que se mostrou ausente aos 180 dias. O implante do cimento de alfa-fosfato tricálcico foi bem tolerado em coelhos, mostrou-se relativamente inerte e permitiu a infiltração de tecido fibrovascular através dos canais de interconexão.
Cimento de alfa-fosfato tricálcico de dupla pega munido de canais de interconexão em coelhos enucleados: um possível implante para cavidade anoftálmica
Keywords: Implant; Eye; Prosthesis; Implante; Olho; Prótese